2010
DOI: 10.2486/indhealth.mswbvi-25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Support Conditions on Vertical Whole-body Vibration of the Seated Human Body

Abstract: Abstract:The vibration transmission to the lumbar and thoracic segments of seated human subjects exposed to whole body vibration of a vehicular nature have been mostly characterised without the back and hand supports, which is not representative of general driving conditions. This non-invasive experimental study investigated the transmission of vertical seat vibration to selected vertebrae and the head along the vertical and fore-aft axes of twelve male human subjects seated on a rigid seat and exposed to rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Briefly, the AM response of each subject seated on the rigid seat was initially measured, where the driving-point force was obtained from the conventionally-used force plate mounted underneath the rigid seat and from the seat mat placed directly on the seat pan. For the experiments, a rigid seat with a 449 £ 456 mm horizontal seat pan and a vertical backrest was mounted on the whole body vertical vibration simulator (WBVVS) platform through a force plate for measurement of the dynamic force at the seat base as described in M-Pranesh, Rakheja, and Demont (2010). The WBVVS was also equipped with a steering column with a steering wheel to provide hands support.…”
Section: Measurement Of Ammentioning
confidence: 99%
“…Briefly, the AM response of each subject seated on the rigid seat was initially measured, where the driving-point force was obtained from the conventionally-used force plate mounted underneath the rigid seat and from the seat mat placed directly on the seat pan. For the experiments, a rigid seat with a 449 £ 456 mm horizontal seat pan and a vertical backrest was mounted on the whole body vertical vibration simulator (WBVVS) platform through a force plate for measurement of the dynamic force at the seat base as described in M-Pranesh, Rakheja, and Demont (2010). The WBVVS was also equipped with a steering column with a steering wheel to provide hands support.…”
Section: Measurement Of Ammentioning
confidence: 99%
“…Furthermore, the contributions of the low inertia subsystems, in particular, are better understood from the 'through-the-body' responses compared to the 'to-the-body' response functions. However, owing to the complexity of vibration measurements of different segments and the errors associated with skin-mounted accelerometers due to relative movements of the skin over the bones [3], the vast majority of the studies have considered the transmission of vibration to the head as an adequate measure of the seated body biodynamics. Wang et al [4] stated that seat-to-head transmissibility (STHT) may be more representative of multiple vibration modes of the upper body than the apparent mass driving-point response.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear behavior of transmissibility has been discussed previously in many studies. 19,26,27 Mansfield and Griffin,19 showed the nonlinear behaviour of apparent mass and transmissibility to the viscera, pelvis, and lumbar spine, and it was observed that the dynamics of tissues, the bending and buckling of the spine, and some complex responses of the body may be the cause for nonlinearity in biodynamic responses.…”
Section: Discussionmentioning
confidence: 99%